Pengaruh Disiplin dan Kompensasi Kerja terhadap Kinerja Karyawan Café di Kota Baturaja - Ruri Yuniarti MJ; Fifian Permata Sari; Rini Efrianti (LPPM Institut Pendidikan Nusantara Global, 2026)
The purpose of this study is to analyze the influence of discipline and compensation on the performance of café employees in Baturaja City, OKU Regency, South Sumatra. The study was conducted in December 2025 in Baturaja City, OKU Regency. The research method used was a quantitative descriptive method with simple random sampling using the Slovin formula, resulting in a sample size of 63 café employees. The results of the study indicate that there is a positive and significant effect on each variable—work discipline and work compensation—separately, and there is a positive and significant effect on the variables of work discipline and work compensation simultaneously or together, with a confidence level or coefficient of determination of 72 percent. It is recommended to improve work discipline and increase compensation levels to enhance the performance of café employees in Baturaja City, OKU.